ORGANOMINERAL FERTILIZER (OMF) AS SUPPLEMENT FOR MAIZE (Zea mays) ACTUATED PHYTOREMEDIATION - Ogungbile, P. O.; Ajibare, A. O.; Ikechukwu, A. O.; Enochoghene, A.; Ogunbode, T. O.; Ogunwale, T.O.; Omotayo, D. O.; Sridhar, M. K. C. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The effectiveness of organo-mineral fertilizer (OMF) in enhancing maize (Zea mays) activated phytoremediation of cadmium (Cd) contaminated soil was investigated around Askar Paints Factory, Eleyele, Ibadan. The experimental site was divided into six plots where maize was cultivated with and without OMF application for 110 days. Pre- and post-harvest soil samples and maize plant tissues were analyzed for Cd levels using Atomic Absorption Spectrophotometry (AAS). Initial cadmium concentrations in the topsoil and subsoil were 31.48±7.82 mg/kg and 31.35±3.72 mg/kg, respectively in OMF-treated plots, compared to 26.96±7.81 mg/kg and 33.50±3.72 mg/kg in the control plots. Post-harvest, Cd levels in the OMF-treated topsoil decreased by 39.17% (to 19.15±9.14 mg/kg) and in the subsoil by 15.18% (to 26.59±3.28 mg/kg). In contrast, control plots showed reductions of 27% and 16.24% in topsoil and subsoil, respectively. These results indicated that OMF significantly improves maize’s ability to remove Cd, particularly from the topsoil. The trend of Cd accumulation in the Control and OMF treated maize was Root > Shoot > Leave > Seed. Analysis of maize plant parts revealed that, OMF treatment increased Cd concentrations in roots (6.30±1.24 mg/kg vs. 4.70±1.73 mg/kg), shoots (4.72±1.53 mg/kg vs. 3.50±1.39 mg/kg), and leaves (2.88±1.96 mg/kg vs. 1.92±1.52 mg/kg), compared to control plants. However, Cd concentrations in seeds were lower in OMF-treated plants (0.61±0.56 mg/kg) compared to control (0.82±0.60 mg/kg). OMF application also positively affected the fresh and dry weights of maize plant parts, with significant increases in root, shoot, leaf, and seed weights in treated plots. This study demonstrated that OMF enhances the phytoremediation efficiency of maize by increasing Cd uptake and translocation to vegetative parts, while potentially reducing Cd accumulation in seeds. Thus, OMF presents a promising approach for improving the phytoremediation of contaminated soils.